Preparation method of white carbon black for rubber base plate of high-speed railway fastener system

By using sodium silicate, sulfuric acid, nonionic active agents and silane coupling agents in the rubber pads of high-speed railway fastener system, the problem of poor dispersion and reinforcement effect of white carbon black in rubber is solved, and the performance of rubber pads is significantly improved and the production cost is reduced.

CN119637883AInactive Publication Date: 2025-03-18FUJIAN ZHENGSHENG INORGANIC MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411535664.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional precipitation method has poor dispersion and reinforcement effect in rubber, resulting in poor performance of rubber pads in high-speed railway fastener system.

Method used

A preparation method including sodium silicate, sulfuric acid, nonionic active agent and silane coupling agent is adopted, and white carbon black with excellent dispersion and reinforcement effects is prepared through a multi-stage acid-base co-flow reaction and spray-drying process.

Benefits of technology

It significantly improves the dispersion stability and reinforcement effect of white carbon black in rubber, improves the dynamic and static stiffness ratio and rebound of the rubber pad, and reduces the use of raw materials and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of white carbon black for a rubber base plate of a high-speed railway fastener system, and belongs to the field of preparation methods of white carbon black, the white carbon black comprises the following raw materials: sodium silicate, sulfuric acid, a nonionic active agent and a silane coupling agent, and the white carbon black is prepared by improving a manufacturing process and setting a specific temperature and a preparation mode. The nonionic active agent and the silane coupling agent can better form specific cooperation, steric hindrance among white carbon black particles is increased, chemical bonding of the white carbon black and the silane coupling agent is enhanced, the reaction efficiency is accelerated, and the reaction environment and stability are optimized, so that agglomeration of the white carbon black particles is prevented, the dispersion effect of the white carbon black in rubber is improved, and the service life of the rubber is prolonged. By setting a two-stage mixing flow rate, uniform primary particles are rapidly formed, gel is reduced, the good state of a reaction system is kept, the particles uniformly grow into balls, the action between the particles and a rubber matrix is enhanced, and the rubber cushion plate is more economical and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation methods of white carbon black, and particularly relates to a preparation method of white carbon black for a rubber pad of a high-speed railway fastener system. Background Art

[0002] In the fastener system of high-speed railway, rubber pads are an important component, playing the role of shock absorption, noise reduction and support. The performance of rubber pads directly affects the operation safety and comfort of high-speed railways. Silica, as a commonly used reinforcing filler, is widely used in the preparation of rubber pads.

[0003] However, the dispersion and reinforcement effects of traditional precipitated silica in rubber are often unsatisfactory. This is mainly because there are a large number of hydroxyl groups on the surface of silica, which makes it highly hydrophilic and difficult to disperse evenly in the rubber matrix. It is easy to agglomerate, thus affecting the performance of the rubber pad.

[0004] At present, commonly used methods include surface modification of silica, optimization of rubber formula and improvement of preparation process, etc. However, these methods still have the problem that improper selection and use of surface modifiers lead to degradation of silica performance, and poor dispersion and reinforcement effects of silica in rubber, thus leading to poor performance of rubber pads. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In order to overcome the shortcomings of the existing technology, a method for preparing white carbon black for rubber pads of high-speed railway fastener systems is proposed to solve the problem that when the existing technology is used, white carbon black agglomerates and affects the performance of the rubber pad, the traditional modification method has poor effect, and the dispersion and reinforcement effects of white carbon black in rubber are poor, which leads to poor performance of the rubber pad.

[0007] (II) Technical solution

[0008] The present invention is implemented by the following technical scheme: The present invention proposes a method for preparing white carbon black for rubber pads of high-speed railway fastener systems, comprising the following raw materials: sodium silicate, sulfuric acid, nonionic active agent and silane coupling agent;

[0009] The following steps are involved:

[0010] S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 5-7m 3 Heat the reaction water to 85-95°C, add the mixture of non-ionic surfactant and silane coupling agent, start stirring, and add sodium silicate and sulfuric acid solution at the same time. The flow rate of sodium silicate is 13.6-14.6m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 7.0-8.0, stop adding acid and alkali until it becomes a suspension, and the reaction time is 20-30min; add 85-95℃ hot water to the reactor, and the volume ratio of water added is 11-13m 3 ;

[0011] S2: Stir at a constant temperature of 85-95°C for 5-15 minutes;

[0012] S3: Continue to add sodium silicate and sulfuric acid to carry out the second stage acid-base co-current reaction. The flow rate of sodium silicate is 6.8-7.3m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.0-11.0, the reaction time is 55-75min, stop the acid and alkali co-flow, and age for 5min;

[0013] S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 3.5-4.5, and age the suspension for 20-40 minutes under heat preservation;

[0014] S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 60-100 μs / cm, the washing is stopped; the filter cake is beaten into slurry by a pulping machine, and the beating time is 1.0 hour;

[0015] S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain white carbon black powder.

[0016] Furthermore, the modulus of the sodium silicate is 3.45-3.60, and water is added to prepare a solution with a sodium silicate concentration of 1.19-1.23 mol / L. The iron content of the prepared sodium silicate solution is below 100 ppm.

[0017] Furthermore, the sulfuric acid is 98% concentrated sulfuric acid which is prepared into 18%-40% dilute sulfuric acid by adding water.

[0018] Furthermore, the nonionic active agent is fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether or fatty acid polyoxyethylene ester.

[0019] Furthermore, the silane coupling agent is a bis-(γ-triethoxysilylpropyl)tetrasulfide coupling agent, γ-aminopropyltriethoxysilane (KH550) or γ-glycidyloxypropyltrimethoxysilane (KH560).

[0020] Furthermore, the nonionic active agent is fatty alcohol polyoxyethylene ether, and the added amount is 0.1%-0.3% of the added amount of sodium silicate.

[0021] Furthermore, the silane coupling agent is bis-(γ-triethoxysilylpropyl) tetrasulfide, and the added amount is 0.5%-1.0% of the added amount of sodium silicate.

[0022] (III) Beneficial effects

[0023] One of the above technical solutions has the following advantages or beneficial effects:

[0024] Under the specific temperature and other conditions of this process, the non-ionic surfactant can reduce the surface tension of the liquid, promote the uniform dispersion of white carbon black in the rubber, and form a protective film on the surface of white carbon black to prevent particle agglomeration. The ability of the non-ionic surfactant to reduce the surface tension of the liquid is enhanced, and a stable protective film can be formed on the surface of white carbon black more quickly and effectively, which not only further increases the steric hindrance between the white carbon black particles and effectively prevents the agglomeration tendency of the particles, but also provides a more suitable environment for the reaction between the silane coupling agent and the hydroxyl groups on the surface of white carbon black.

[0025] The activity of the silane coupling agent is enhanced, and the chemical reaction rate with the hydroxyl group on the surface of white carbon black is accelerated, so that it can be more firmly combined with white carbon black. In addition, the presence of the non-ionic active agent protective film reduces the interference of external factors on the reaction of the silane coupling agent, so that the silane coupling agent can be more accurately combined with the active sites on the surface of white carbon black, further enhancing the dispersion stability of white carbon black in the system. Under the synergistic effect of temperature, the two have achieved significant optimization of the dispersion effect, far exceeding the effect under normal temperature or other temperature conditions, so that the produced white carbon black has good dispersion and reinforcement effects, and the dynamic and static stiffness ratio of the rubber pad becomes smaller, and the resilience is enhanced. The raw materials are low-iron sodium silicate and low-conductivity water, which ensures the purity of the product;

[0026] Finally, under the specific temperature and process conditions of the present application, the amount of nonionic surfactant and silane coupling agent added can be reduced under the same or even better dispersion effect and performance requirements compared to the prior art, which can save production costs and have better environmental benefits. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0028] The present invention provides a method for preparing white carbon black for rubber pads of high-speed railway fastener systems, comprising the following raw materials: sodium silicate, sulfuric acid, a nonionic active agent and a silane coupling agent;

[0029] The following steps are involved:

[0030] S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 5-7m 3Heat the reaction water to 85-95°C, add the mixture of non-ionic surfactant and silane coupling agent, start stirring, and add sodium silicate and sulfuric acid solution at the same time. The flow rate of sodium silicate is 13.6-14.6m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 7.0-8.0, stop adding acid and alkali until it becomes a suspension, and the reaction time is 20-30min; add 85-95℃ hot water to the reactor, and the volume ratio of water added is 11-13m 3 ;

[0031] S2: Stir at a constant temperature of 85-95°C for 5-15 minutes;

[0032] S3: Continue to add sodium silicate and sulfuric acid to carry out the second stage acid-base co-current reaction. The flow rate of sodium silicate is 6.8-7.3m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.0-11.0, the reaction time is 55-75min, stop the acid and alkali co-flow, and age for 5min;

[0033] S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 3.5-4.5, and age the suspension for 20-40 minutes under heat preservation;

[0034] S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 60-100 μs / cm, the washing is stopped; the filter cake is beaten into slurry by a pulping machine, and the beating time is 1.0 hour;

[0035] S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain white carbon black powder.

[0036] The modulus of the sodium silicate is 3.45-3.60, and water is added to prepare a solution with a sodium silicate concentration of 1.19-1.23 mol / L. The iron content of the prepared sodium silicate solution is below 100 ppm.

[0037] The sulfuric acid is 98% concentrated sulfuric acid which is prepared into 18%-40% dilute sulfuric acid by adding water.

[0038] Wherein, the nonionic active agent is fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether or fatty acid polyoxyethylene ester.

[0039] Wherein, the silane coupling agent is bis-(γ-triethoxysilylpropyl) tetrasulfide coupling agent, γ-aminopropyltriethoxysilane (KH550) or γ-glycidyloxypropyltrimethoxysilane (KH560).

[0040] Wherein, the nonionic active agent is fatty alcohol polyoxyethylene ether, and the added amount is 0.1%-0.3% of the added amount of sodium silicate.

[0041] Wherein, the silane coupling agent is bis-(γ-triethoxysilylpropyl) tetrasulfide, and the added amount is 0.5%-1.0% of the added amount of sodium silicate.

[0042] Under this process:

[0043] 1. Significant optimization of dispersion effect in a specific temperature range under synergistic effect

[0044] 1. Temperature promotes synergistic mechanisms

[0045] Under the temperature condition of 85-95℃, the ability of non-ionic surfactant to reduce the surface tension of liquid is enhanced, and it can form a stable protective film on the surface of silica more quickly and effectively. This not only further increases the steric hindrance between silica particles, effectively preventing the agglomeration tendency of particles, but also provides a more suitable environment for the reaction between silane coupling agent and silica surface hydroxyl group.

[0046] The activity of the silane coupling agent is enhanced in this temperature range, and the chemical reaction rate with the hydroxyl groups on the surface of silica is accelerated, so it can be more firmly bonded to silica. At the same time, the presence of the non-ionic surfactant protective film reduces the interference of external factors on the reaction of the silane coupling agent, allowing the silane coupling agent to more accurately bind to the active sites on the surface of silica, further enhancing the dispersion stability of silica in the system. Under the synergistic effect of temperature, the two promote each other through various mechanisms, achieving a significant optimization of the dispersion effect, far exceeding the effect at room temperature or other temperature conditions.

[0047] Among them, the various mechanisms refer to the reduction of surface tension and steric hindrance by the non-ionic surfactant in this process: effectively reducing the surface tension of the liquid, forming a protective film on the surface of silica, increasing the steric hindrance between particles, and preventing agglomeration; improving hydrophilicity: reducing the hydrophilicity of the silica surface, improving the compatibility with the rubber matrix, etc., and facilitating dispersion in the rubber.

[0048] Enhanced chemical bonding of silane coupling agent: enhanced activity, rapid reaction with the surface hydroxyl groups of silica to form chemical bonds, reducing the number of hydroxyl groups and surface energy, and enhancing the bonding force with rubber; directional arrangement and interface compatibility: after the reaction, directional arrangement at the interface, adjusting the interface properties, reducing the interface energy, and improving the compatibility with the rubber matrix.

[0049] Temperature synergistically accelerates molecular motion and reaction rate: speeds up molecular thermal motion, allowing the two to diffuse rapidly and interact with each other, accelerating reactions and improving efficiency; optimizes reaction environment and stability: provides a stable environment, reduces interference, makes synergy more coordinated and orderly, and optimizes dispersion effects.

[0050] 2. Positive impact on micro and macro dispersion performance

[0051] On a microscopic level, at 85-95°C, the synergistic effect of the non-ionic surfactant and the silane coupling agent improves the surface properties of the silica particles to a more ideal level, further reduces the hydrophilicity of the silica surface, and significantly improves the compatibility with the rubber matrix. The interaction force between the particles is more accurately regulated at this temperature, allowing the silica particles to be distributed in the system in a more uniform and independent state, laying a solid foundation for subsequent good dispersion in the rubber matrix.

[0052] In terms of macroscopic performance, when this kind of silica co-treated at a specific temperature is applied to the rubber pad, the mechanical properties of the rubber are more significantly improved. For example, the tensile strength, rebound resilience and other indicators of the rubber are significantly improved compared with the silica prepared under other temperature conditions, and the dynamic-static stiffness ratio is further reduced. This fully demonstrates that within the temperature range of 85-95°C, the synergistic effect of the non-ionic surfactant and the silane coupling agent enables the dispersion effect of silica in the rubber matrix to reach a better level, thereby greatly improving the comprehensive performance of the rubber pad.

[0053] Among them, when the temperature is lower than the range of this process: the synergistic effect of the non-ionic surfactant and the silane coupling agent in this process is weakened, the ability of the non-ionic surfactant to reduce surface tension and to form a protective film on the surface of silica becomes worse, the reaction rate of the silane coupling agent with the surface hydroxyl group of silica slows down, the combination of the two is disturbed, and the dispersion stability of silica decreases.

[0054] Among them, when it is higher than or lower than the range of this process: the synergistic effect of the non-ionic surfactant and the silane coupling agent of this process is changed, the stability of the non-ionic surfactant is affected, and it is easy to decompose or fail, the silane coupling agent over-reacts or abnormally, resulting in unsatisfactory bonding effect, and the risk of agglomeration of silica particles increases.

[0055] 2. Optimization and advantages of usage in a specific temperature range under synergistic effect

[0056] 1. The impact of temperature on usage demand

[0057] Under the temperature condition of 85-95℃, the synergistic efficiency of nonionic surfactant and silane coupling agent is significantly improved. Since the activity and reaction rate of both are improved in this temperature range, their usage can be further reduced while achieving the same or even better dispersion effect and performance requirements. For example, compared with the use at lower or higher temperatures, at 85-95℃, the addition amount of nonionic surfactant is 0.1%-0.3% of the amount of sodium silicate to achieve a good dispersion effect, and the addition amount of silane coupling agent is 0.5%-1.0% of the amount of sodium silicate to fully play its role, which is significantly reduced compared with the conventional dosage under other temperature conditions.

[0058] 2. Comprehensive benefits

[0059] In terms of cost-effectiveness, the reduction in usage at a specific temperature not only reduces the cost of raw materials, but also reduces energy consumption and waste emissions in the production process, bringing significant economic and environmental benefits to the company. At the same time, from the perspective of production process stability and product quality, at 85-95°C, the synergistic effect of non-ionic surfactants and silane coupling agents is more stable and controllable, which can effectively reduce product performance differences caused by dosage fluctuations or temperature changes, improve production efficiency and product consistency, and further enhance product competitiveness in the market.

[0060] Among them, in this process, when the temperature is lower than this process temperature, such as 30-55℃:

[0061] To achieve similar effects, the amount of non-ionic surfactants added must be 0.5%-1.0% or even higher than that of sodium silicate. Because the activity decreases at low temperatures, the amount must be increased to achieve dispersion of white carbon black particles. For example, the amount of fatty alcohol polyoxyethylene ether in room temperature experiments often needs to be close to or exceed 0.5%;

[0062] Silane coupling agent has a slow reaction rate, and the amount added may need to be around 1.5%-2.5% of sodium silicate. At low temperatures, molecular motion slows down, and more amount is needed to react with the surface hydroxyl groups of silica. For example, the amount of γ-aminopropyltriethoxysilane (KH550) used at room temperature is relatively high.

[0063] At higher temperatures, above 100°C:

[0064] The stability of non-ionic surfactants is affected, and the added amount still needs to be around 0.3%-0.6% of sodium silicate. Although the ability to reduce surface tension will be slightly enhanced, some of them will decompose or change their structure. For example, fatty alcohol polyoxyethylene ether decomposes faster at high temperatures, so a certain amount needs to be maintained to ensure the dispersion effect.

[0065] Silane coupling agents accelerate the reaction rate but are prone to side reactions. The amount added is about 0.8%-1.5% of sodium silicate. For example, the amount of bis-(γ-triethoxysilylpropyl)tetrasulfide coupling agent at high temperature needs to balance the reaction rate and product quality. Too low an amount may cause local overreaction, while too high an amount may cause too many side reactions.

[0066] At the same time, this application sets the first stage flow rate to 13.6-14.6m 3 / h, which can quickly initiate the reaction to generate primary particles. A low flow rate will slow down the reaction start-up and lead to insufficient particle generation. At the same time, it can avoid local excessive concentration of sodium silicate to form gel, so as to ensure a smooth reaction and quickly form uniform primary particles, lay a foundation for subsequent growth, reduce gel, maintain the reaction system in a good state, and facilitate the subsequent reaction.

[0067] Set the second stage flow rate to 6.8-7.3m 3 / h, can accurately control particle growth, high flow rate will lead to uneven particle size, adapt to the dynamic conditions of system property changes during reaction advancement, achieve uniform growth of particles into spheres, enhance interaction with rubber matrix, significantly improve rubber mechanical properties, reduce dynamic-static stiffness ratio, and improve product value and competitiveness.

[0068] Embodiment 1:

[0069] Raw materials preparation:

[0070] Sodium silicate: The modulus is 3.50, the concentration is 1.23 mol / L, and the iron content of the prepared sodium silicate solution is less than 100 ppm.

[0071] Sulfuric acid: Sulfuric acid with a mass concentration of 30%.

[0072] Nonionic surfactant: fatty alcohol polyoxyethylene ether, the added amount is 0.1% of the added amount of sodium silicate.

[0073] Silane coupling agent: bis-(γ-triethoxysilylpropyl) tetrasulfide, the added amount is 0.5% of the added amount of sodium silicate.

[0074] The conductivity of water used for preparing sodium silicate / sulfuric acid, reaction and washing is 50μs / cm.

[0075] Reaction process:

[0076] S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 6m 3 The reaction water was heated to 90°C, and a mixture of nonionic surfactant and silane coupling agent was added. Stirring was started, and sodium silicate and sulfuric acid solution were added at the same time. The flow rate of sodium silicate was 13.6 m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 7.5, stop adding acid and alkali until it becomes a suspension, and the reaction time is 25min; add 90℃ hot water to the reactor, and the volume ratio of water added is 12m 3 .

[0077] S2: Stir at a constant temperature of 90°C for 10 min.

[0078] S3: Continue to add sodium silicate and sulfuric acid to carry out the second-stage acid-base co-current reaction. The flow rate of sodium silicate is 6.8m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.5. The reaction time is 65min, and after stopping the acid and alkali co-flow, age for 5min.

[0079] S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 4.0, and age the suspension for 30 minutes under heat preservation.

[0080] Post-processing:

[0081] S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 80 μs / cm, the washing is stopped; the filter cake is beaten into slurry with a pulping machine, and the beating time is 1.0 hour.

[0082] S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain precipitated silica powder.

[0083] Embodiment 2:

[0084] Raw materials preparation:

[0085] Sodium silicate: The modulus is 3.50, the concentration is 1.23 mol / L, and the iron content of the prepared sodium silicate solution is less than 100 ppm.

[0086] Sulfuric acid: Sulfuric acid with a mass concentration of 18%.

[0087] Nonionic surfactant: fatty alcohol polyoxyethylene ether, the added amount is 0.3% of the added amount of sodium silicate.

[0088] Silane coupling agent: bis-(γ-triethoxysilylpropyl) tetrasulfide, the added amount is 1.0% of the added amount of sodium silicate.

[0089] The conductivity of water used for preparing sodium silicate / sulfuric acid, reaction and washing is 50μs / cm.

[0090] Reaction process:

[0091] S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 7m 3The reaction water was heated to 95°C, and a mixture of nonionic surfactant and silane coupling agent was added. Stirring was started, and sodium silicate and sulfuric acid solution were added at the same time. The flow rate of sodium silicate was 14.6m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 7.5, stop adding acid and alkali until it becomes a suspension, and the reaction time is 25min; add 95℃ hot water to the reactor, and the volume ratio of water added is 12m 3 .

[0092] S2: Stir at constant temperature (95°C) for 10 min.

[0093] S3: Continue to add sodium silicate and sulfuric acid to carry out the second stage acid-base co-current reaction. The flow rate of sodium silicate is 7.3m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.5. The reaction time is 65min, and after stopping the acid and alkali co-flow, age for 5min.

[0094] S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 4.5, and age the suspension for 30 minutes under heat preservation.

[0095] Post-processing:

[0096] S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 80 μs / cm, the washing is stopped; the filter cake is beaten into slurry with a pulping machine, and the beating time is 1.0 hour.

[0097] S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain precipitated silica powder.

[0098] Embodiment three:

[0099] Raw materials preparation:

[0100] Sodium silicate: The modulus is 3.50, the concentration is 1.23 mol / L, and the iron content of the prepared sodium silicate solution is less than 100 ppm.

[0101] Sulfuric acid: Sulfuric acid with a mass concentration of 24%.

[0102] Nonionic surfactant: fatty alcohol polyoxyethylene ether, the added amount is 0.2% of the added amount of sodium silicate.

[0103] Silane coupling agent: bis-(γ-triethoxysilylpropyl) tetrasulfide, the added amount is 0.8% of the added amount of sodium silicate.

[0104] The conductivity of water used for preparing sodium silicate / sulfuric acid, reaction and washing is 50μs / cm.

[0105] Reaction process:

[0106] S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 6m 3 The reaction water was heated to 92°C, and a mixture of nonionic surfactant and silane coupling agent was added. Stirring was started, and sodium silicate and sulfuric acid solution were added at the same time. The flow rate of sodium silicate was 13.9 m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 8.0, stop adding acid and alkali until it becomes a suspension, and the reaction time is 25min; add 92℃ hot water to the reactor, and the volume ratio of water added is 11m 3 .

[0107] S2: Stir at constant temperature (92°C) for 10 min.

[0108] S3: Continue to add sodium silicate and sulfuric acid to carry out the second-stage acid-base co-current reaction. The flow rate of sodium silicate is 7.1m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.0. The reaction time is 65min, and after stopping the acid and alkali co-flow, age for 5min.

[0109] S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 4.0, and age the suspension for 30 minutes under heat preservation.

[0110] Post-processing:

[0111] S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 80 μs / cm, the washing is stopped; the filter cake is beaten into slurry with a pulping machine, and the beating time is 1.0 hour.

[0112] S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain precipitated silica powder.

[0113] Comparative Example 1:

[0114] The difference from Example 1 is that no nonionic surfactant is added during the reaction, and other conditions are the same as Example 1.

[0115] Comparative Example 2:

[0116] The difference from Example 1 is that no silane coupling agent is added during the reaction, and the other conditions are the same as Example 1.

[0117] Comparative Example 3:

[0118] The difference from Example 1 is that the nonionic active agent and the silane coupling agent are not added during the reaction process, and the other conditions are the same as those of Example 1.

[0119] The dispersion and reinforcement effect of white carbon black in rubber is reflected by the mechanical properties, dynamic and static stiffness ratio, and resilience of the rubber. The testing technical indicators of the white carbon black product obtained in the above embodiment are listed in the following table:

[0120]

[0121] From the above data, it can be seen that the dispersion effect and reinforcement effect of the white carbon black product prepared in the example in rubber are significantly better than those of the comparative example product, the dynamic-static stiffness ratio is smaller, and the resilience is better. This fully proves the importance of the synergistic effect of the nonionic active agent and the silane coupling agent in improving the performance of white carbon black.

[0122] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0123] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing white carbon black for rubber pads of high-speed railway fastener systems, characterized in that: Including the following ingredients: Sodium silicate, sulfuric acid, non-ionic surfactant and silane coupling agent; The following steps are involved: S1: at 40m 3 In a stainless steel reactor with high-speed stirring, add 5-7m 3 Heat the reaction water to 85-95°C, add the mixture of non-ionic surfactant and silane coupling agent, start stirring, and add sodium silicate and sulfuric acid solution at the same time. The flow rate of sodium silicate is 13.6-14.6m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 7.0-8.0, stop adding acid and alkali until it becomes a suspension, and the reaction time is 20-30min; add 85-95℃ hot water to the reactor, and the volume ratio of water added is 11-13m 3 ; S2: Stir at a constant temperature of 85-95℃ for 5-15min; S3: Continue to add sodium silicate and sulfuric acid to carry out the second-stage acid-base co-current reaction. The flow rate of sodium silicate is 6.8-7.3m 3 / h, adjust the sulfuric acid flow rate, control the pH of the reaction process to be stable at 10.0-11.0, the reaction time is 55-75min, stop the acid and alkali co-flow, and age for 5min; S4: Continue to add sulfuric acid to the reactor to adjust the pH value of the suspension to 3.5-4.5, and age the suspension for 20-40 minutes under heat preservation; S5: The suspension obtained by the reaction is separated into solid and liquid, and the filter cake is washed with water. When the conductivity of the plate and frame filtered water reaches 60-100μs / cm, the washing is stopped; the filter cake is beaten into slurry with a pulping machine, and the beating time is 1.0 hour; S6: spray drying is performed using a high-speed centrifugal spray dryer to obtain white carbon black powder.

2. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 1, characterized in that: The modulus of the sodium silicate is 3.45-3.60, and water is added to prepare a solution with a sodium silicate concentration of 1.19-1.23 mol / L. The iron content of the prepared sodium silicate solution is below 100 ppm.

3. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 1, characterized in that: The sulfuric acid is 98% concentrated sulfuric acid mixed with water to make 18%-40% dilute sulfuric acid.

4. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 1, characterized in that: The nonionic active agent is fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether or fatty acid polyoxyethylene ester.

5. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 1, characterized in that: The silane coupling agent is a bis-(γ-triethoxysilylpropyl) tetrasulfide coupling agent, γ-aminopropyltriethoxysilane (KH550) or γ-glycidyloxypropyltrimethoxysilane (KH560).

6. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 4, characterized in that: The nonionic active agent is fatty alcohol polyoxyethylene ether, and the added amount is 0.1%-0.3% of the added amount of sodium silicate.

7. The method for preparing white carbon black for rubber pads of high-speed railway fastener systems according to claim 5, characterized in that: The silane coupling agent is bis-(γ-triethoxysilylpropyl) tetrasulfide, and the added amount is 0.5%-1.0% of the added amount of sodium silicate.

Citation Information

Patent Citations

  • Preparation method of modified precipitated white carbon black

    CN102951649A

  • Preparation method of high-transparency high-dispersity white carbon black

    CN103303929A

  • Preparation method of white carbon black with high structure and high oil absorption value

    CN113861724A

  • Hydrophobic high-dispersion white carbon black as well as preparation method and application thereof

    CN114286801A